An Agenda for Sustainable Operations and Supply Chain Management Research - Miemczyk, Joe (Brazilian Journal of Operations & Production Management, 2013)
The purpose of this paper is to review some of the key challenges to sustainable operationsand supply chain management and provide future research directions. While sustainabilityand sustainable development is defined in many ways, the principles of integrating economic,environmental and social imperatives are well understood. Despite an expanding understandingof the implications of sustainability, research to date, as well as practical implementation, reveals many areas for further development. Sustainability is a particularly difficult subject to researchwhich raises many trade-off situations. As examples, there are conflicts between differentenvironmental factors (energy and waste) when taking a life cycle perspective and burgeoninginstitutional constraints limit the economic degrees of freedom (limiting opportunities for closedloop solutions). Drawing on past experiences, recent research and current practices, this article provides a framework for future research in sustainable operations and supply chain management.